Effect of Boerhavia diffusa and Bryophyllum calycinum Extracts on Urine Profile in Male Wistar Rats having Adenineinduced Chronic Kidney Disease - Singh, Madhu; Raval, Sunant K.; Modi, Rakeshkumar J.; Sadhu, Dashrath; Dave, Keshank (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was conducted on 62 adult healthy male Wistar rats (12-15 weeks of age) to examine the effect of herbal extracts on urineprofile following adenine-induced chronic kidney disease (CKD). The rats were randomly divided into eight groups. Group I (n=6) wasgiven only distilled water and served as healthy control. The rats of groups II to VIII (n=8 each) were given adenine @ 200 mg/kg bodyweight daily by oral gavage needle for 28 days to induce CKD. After 28th day, group II served as CKD positive group, while groups III andIV were given aqueous and alcoholic extract of Boerhavia diffusa (BD), group-V and VI with aqueous and alcoholic extract of Bryophyllumcalycinum (BC) @ 300 mg/kg body weight daily for 42 days. Group VII was given bihebral aqueous extract of BC plus BD (1:1.5), whilegroup VIII received bihebral alcoholic extract of BC and BD (1:1.5) @ 300 mg/kg body weight daily for 42 days. Urine parameters werestudied on day 0, 28 and 70 of experiment to confirm the presence of CKD. Significantly (p
Keywords: : Boerhavia diffusa, Bryophyllum calycinum, Herbal extracts; Nephroprotective effect, Urine analysis; Wistar rats